Improving performance, reproduction, and immunity in laying Japanese quail with algal derivatives - Hassan Habibi; Enayat Rahmatnejad; Sayyed Sattar Tohidifar; Alireza Afshar; Ali Kameli; Maryam Jafari; Mehdi Mohammadi (Poultry Science, 2024)
ABSTRACT: We investigated the effect of the Persian Gulf algae derivatives, namely phycocyanin (PC) and fucoidan (FUC), on the performance, reproductive traits, and immune responses of laying Japanese quails. A completely randomized design was used to distribute 250 six-wk-old Japanese quails with an average body weight of 215 ± 10 g into 5 treatments, 5 replicates, and 10 birds in each replicate over a 5-wk period. Unlike the control groups, the treatment groups received drinking water supplemented with PC and FUC at concentrations of 20 or 40 mg/L, denoted as PC20, PC40, FUC20, and FUC40, respectively, while all birds were provided with identical feed. Supplemental algal derivatives notably improved hen day egg production (HDEP), egg mass, and feed conversion ratio (FCR) compared to the control group (P < 0.01). Incorporating PC and FUC had no significant effect on the weight of males' testes or the weight and length of hens' oviducts. Additionally, the experimental treatments had no impact on the chicks' hatching weight. The supplementation of PC and FUC resulted in increased fertility (P = 0.038) and hatchability (P < 0.001) rates, with the exception of fertility in the PC40 group. The effect of the experimental treatments on immune responses was largely not statistically significant, except in the case of ND. Specifically, the experimental treatments resulted in increased (P = 0.033) antibody titers against ND when compared to the control group, with the exception of FUC20. Supplemental algal derivatives significantly (P < 0.01) reduced total cholesterol, creatinine, and triglycerides (except in the case of PC20). Overall, these findings underscore the potential of algal derivatives to enhance quail performance, reproductive traits, and immune responses.